Dissolved munition compounds in the water column of southwestern Baltic Sea during ALKOR cruise AL567 - Aaron Beck; Kenneth Arinaitwe; Jens Greinert; Eric Pieter Achterberg (PANGAEA, 2025)
Cruise AL567 (R/V Alkor) sampled the water column in German territorial waters of the southwest Baltic Sea during 18-30 October 2021. This dataset contains concentrations of dissolved munition compounds from 88 Niskin bottle rosette casts between sea surface and seafloor. Samples were collected at the sea surface (1-2 m depth), approximately 2 m above the seafloor, and immediately below the pycnocline. Dissolved explosives in the samples were measured following Gledhill et al. (2019). Briefly, discrete samples (1 L) were preconcentrated onboard using solid-phase extraction. Target compounds were eluted with acetonitrile, further concentrated by evaporation, and measured by ultra-high performance liquid chromatography and high resolution heated electrospray ionization mass spectrometry.